1976
DOI: 10.1002/ijc.2910180411
|View full text |Cite
|
Sign up to set email alerts
|

Surface glycoproteins and concanavalin‐A‐mediated agglutinability of clonal variants and tumour cells derived from SV40‐virus‐transformed mouse 3T3 cells

Abstract: Cell strains isolated from an established line of SV40-transformed mouse 3T3 cells (SV3T3) showed large variations in the various parameters of transformation, viz. saturation density, serum requirement, contact inhibition of movement and of growth and Concanavalin-A-mediated agglutinability. These cell strains were studied for changes in elution profiles of fucose-labelled surface glycoproteins, using actively growing, untransformed 3T3 cells as controls. A cell strain established from a tumour arising after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

1977
1977
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Bordelon [24], Shields [8] reported that there was no corre lation between this test and the transformed phenotype. It is nevertheless of value in confirming previously obtained results [7,19] or in certain cell systems [25]. In the same way, the SD1 and A9/SEWA hybrid cell lines, derived from the common SEWA parent, show very similar agglutination ability to Con A, a similar ability to form colonies in soft agar and the same saturation density.…”
Section: Discussionsupporting
confidence: 85%
“…Bordelon [24], Shields [8] reported that there was no corre lation between this test and the transformed phenotype. It is nevertheless of value in confirming previously obtained results [7,19] or in certain cell systems [25]. In the same way, the SD1 and A9/SEWA hybrid cell lines, derived from the common SEWA parent, show very similar agglutination ability to Con A, a similar ability to form colonies in soft agar and the same saturation density.…”
Section: Discussionsupporting
confidence: 85%
“…The solid tumors originating from the transfectants were explanted in vitro using collagenase, hyaluronidase and pronase (Smets et al, 1976). Tumor cells were cultured in vitro for further characterization.…”
Section: Test For Tumorigenicitymentioning
confidence: 99%
“…The tumorigenicity of tumor-DNA-induced transfectants was tested by S.C. inoculation of 500,000 cells in the posterior side of the neck of 2 to 3-month-old c3H nude mice. The solid tumors originating from the transfectants were explanted in vitro using collagenase, hyaluronidase and pronase (Smets et al, 1976). Tumor cells were cultured in vitro for further characterization.…”
Section: Test For Tumorigenicitymentioning
confidence: 99%
“…However, more extended studies have recently shown that these phenomena are 11 not, or are not generally, characteristic of tumourigenic cells (Kolata, 1975;Shin et al, 1975;Hynes, 1976;Nicolson, 1976;Shields, 1976;Smets, Van Beek and Van Rooij, 1976;Nilsson et al, 1977). These findings underline the importance of extending investigations to several cell systems.…”
mentioning
confidence: 99%